Cancer Therapy: Core–Shell–Satellite Nanomaces as Remotely Controlled Self‐Fueling Fenton Reagents for Imaging‐Guided Triple‐Negative Breast Cancer‐Specific Therapy (Small 31/2020). Issue 31 (6th August 2020) - Du, Yang; Yang, Chuang; Li, Fangyuan; Liao, Hongwei; Chen, Zheng; Lin, Peihua; Wang, Nan; Zhou, Yan; Lee, Ji Young; Ding, Qiang; Ling, Daishun
Abstract : In article number 2002537, Fangyuan Li, Qiang Ding, Daishun Ling, and co‐workers report core–shell–satellite nanomaces composed of mesoporous silica coated gold nanorod and surface grafted ultrasmall iron oxide nanoparticles. By exploiting the vulnerability of iron efflux in triple‐negative breast cancer (TNBC) cells, the nanomaces exhibit a photothermal enhanced Fenton reaction‐mediated anti‐cancer effect under near‐infrared laser irradiation for specific TNBC therapy.